Chiral-Lattice-Filled Composite Tubes under Uniaxial and Lateral Quasi-Static Load: Experimental Studies - Kadir Günaydın; Aykut Tamer; Halit S. Türkmen; Giuseppe Sala; Antonio Mattia Grande; Türkmen, Halit Süleyman (MDPI AG, 2021)
Our research investigated the energy absorption characteristics of chiral auxetic lattices filled cylindrical composite tubes subjected to a uniaxial and lateral quasi-static load. The lattice structures were manufactured using a 3D printing technique. Carbon fiber composite tubes without filler material were initially subjected to uniaxial and lateral quasi-static crushing load. The same types of experiment were then performed on chiral lattices and chiral lattices filled composite tubes. For the different cases, the load–displacements curves were analyzed and the specific energy absorption (SEA) values were compared. The SEA capability for the axial quasi-static crushing of the chiral lattices filled composite tubes decreased in comparison with the hollow composite design. However, the most significant result was that the average SEA value in the case of lateral loading increased dramatically in comparison with the hollow composite configuration.
Keywords: Technology; IMPACT; Chemistry, Multidisciplinary; FOS: Mechanical engineering; Auxetic Materials; Auxetics; Engineering; DESIGN; Biology (General); Multidisciplinary; Physics; crushing; Composite number; MECHANICAL-PROPERTIES; HONEYCOMB; D printing; Engineering (General). Civil engineering (General); Chemistry; Biomechanics of Traumatic Brain Injury; Manufacture and Application of Cellular Materials; Applied; Physical Sciences; Medicine; TA1-2040; BEHAVIOR; Pulmonary and Respiratory Medicine; Composite material; QH301-705.5; QC1-999; Energy Absorption; Materials Science; Engineering, Multidisciplinary; Materials Science, Multidisciplinary; FIBER; Physics, Applied; Health Sciences; energy absorption; COLLAPSE; QD1-999; chiral auxetics; Science & Technology; Mechanical Engineering; composite tube; Acoustics; Lattice (music); AXIAL CRUSH; Materials science; D Printing Technologies; ENERGY-ABSORPTION; STACKING-SEQUENCE